Variation of adult Great Tit Parus major body condition and blood parameters in relation to sex, age, year and season - Norte, A; Ramos, J; Sousa, J; Sheldon, B (2009)
In recent years, an increasing number of studies have focused on the ranges of variation of health related biochemical and haematological parameters in wildlife, but information is still scarce for enzymatic activities which can be extremely important in detecting potential responses to environmental change. In a Great Tit (Parus major) population, we describe the variation in relation to age, sex, season and year of: (1) morphological: body condition index, fat and muscle, (2) haematological: hematocrit, haemoglobin, white blood cell count and heterophil/lymphocyte ratio, and (3) biochemical parameters: plasma protein and activities of plasma cholinesterases (acetylcholinesterase and butyrylcholinesterase) activity and red blood cell glutathione peroxidase. Sex had significant effects on all morphological parameters except fat. Age significantly affected cholinesterase activities, H/L ratio and haemoglobin, and there was a significant interaction between sex and age affecting hematocrit. There were significant interactions of year and season affecting almost all parameters studied - body condition index, fat, protein, acetyl and butyrylcholinesterase activities, glutathione peroxidase activity and haemoglobin. This study indicates that these parameters are largely influenced by year and seasonal effects, besides the individual's intrinsic variation. Therefore, when evaluating experimental or environmental change effects, appropriate controls should be used. © Dt. Ornithologen-Gesellschaft e.V. 2009.